First report of Rickettsia conorii in Hyalomma kumari ticks - Ullah, Shafi (2023)
As a vector of wide range of pathogenic agents, ticks pose health threats to wild and domestic animals, and humans. Information is unavailable about the prevalence and spatial survey of Hyalomma kumari ticks and associated Rickettsia spp. in Pakistan. Concerning this knowledge gap, the present study aimed to molecularly detect Rickettsia species associated with H. kumari infesting small ruminants in Khyber Pakhtunkhwa (KP), Pakistan. A total of 409 H. kumari ticks were collected from 163/295 infested hosts with an infestation rate of 55.25%. A total of 204 females, 158 males, and 47 nymphs were collected. Goats were heavily infested by 224 ticks having an infestation rate of 58.33% (98/168), whereas sheep were infested by 185 ticks having a lesser infestation rate of 51.18% (65/127). Genomic DNA extracted from ticks was used for the amplification of tick (cox I, 16S rRNA, ITS-2) species and Rickettsia (gltA, ompA, and ompB) partial genes. Eighty-three ticks were subjected to PCR, and 8/83 (9.6%) were found positive for rickettsial agents. The cox I and 16S rRNA sequences of H. kumari showed 98.90–99.74% identity with H. kumari sequences reported from Pakistan, and phylogenetically clustered to the corresponding species reported from Pakistan and India. The obtained rickettsial gltA, ompA, and ompB sequences showed 100% identity with Rickettsia sp. of the Rickettsia conorii reported from Pakistan. In the phylogenetic trees, rickettsial sequences clustered with uncharacterized Rickettsia sp. from Pakistan and R. conorii from Israel, Russia, South Africa, and India. The present molecular based detection of H. kumari-associated R. conorii will facilitate effective surveillance in the region.